Directional aiming bias in golf putting - Shim, J.; Chung, H.; Kim, J. (Journal of Sports Sciences, 2019)
Johnston, Benton, and Nishida (2003, Last but not least - Golfers may have to overcome a persistent visuospatial illusion. Perception, 32(9), 1151-1154) reported that when standing sideways to hit a golf ball, it becomes very difficult to see the veridical line of putt to the target and it creates a bias to misread the direction to the right of target. The purpose of the study was to determine if this perceptual aiming bias also impacts putting. A group of expert (N = 24) and novice (N = 24) players performed a perception task of aligning a line on the golf ball towards the target hole and an action task of putting a ball to the target hole located 1 m and 4 m away. Novice players showed large perceptual aiming bias and small action aiming bias of putting. Yet, expert players showed neither bias in perceptual aiming nor in putting. This replicates earlier work (van Lier, van der Kamp, & Savelsbergh, 2011 Perception action in golf putting: Skill differences reflect calibration. Journal of Sport & Exercise Psychology, 33(3), 349-369) and was explained by the two-visual-pathway hypothesis. Despite the results showing some favorable support for the two-visual-pathway hypothesis, possible limitations are discussed.